2019
DOI: 10.1002/mar.21245
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the marketing impact of consumers’ connectedness to celebrity endorsers

Abstract: Consumers enjoy following famous media personalities, discovering details about their habits, food preferences, or designer brands that they wear. Consumers model their consumption behaviors based on their favorite celebrities' preferences. Marketers are aware of such celebrity admiration and frequently use celebrities as part of marketing communication strategies. Grounded in parasocial relationship and social connectedness theories, this study tests a model of connectedness to the celebrity, attitude toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 56 publications
4
32
0
4
Order By: Relevance
“…Existent literature provides robust evidence that parasocial relationships increase the persuasiveness of the counterpart. Consumers accepted the counterpart's (e.g., media figures and avatars) arguments and suggestions more readily when they have built parasocial relationships with them (Chung & Cho, 2017; Colliander & Dahlén, 2011; Tran et al, 2019). Chung and Cho (2017) studied parasocial relationships between a celebrity endorser and users on social media and found that parasocial relationships increased source trustworthiness and purchase intentions.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Existent literature provides robust evidence that parasocial relationships increase the persuasiveness of the counterpart. Consumers accepted the counterpart's (e.g., media figures and avatars) arguments and suggestions more readily when they have built parasocial relationships with them (Chung & Cho, 2017; Colliander & Dahlén, 2011; Tran et al, 2019). Chung and Cho (2017) studied parasocial relationships between a celebrity endorser and users on social media and found that parasocial relationships increased source trustworthiness and purchase intentions.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Verbal communication plays a key role in building relationships (Berger & Calabrese, 1975) and relationship building is a critical element of sales. Consumers can be easily persuaded by people they have close relationships with and feel connected to (e.g., Nass & Yen, 2010; Tran et al, 2019), including family members, friends, and sales associates. During shopping, the voice assistant performs the role of a sales associate by providing recommendations, product information, and payment assistance.…”
Section: Introductionmentioning
confidence: 99%
“…The mentioned attractiveness does not only mean the attractiveness of physical properties but also elegance (Mills & Aronson, 1965), and sexuality (Steadman, 1969). Tran et al (2019) tried to explain how influencers lead consumers to positive attitudes and behavioral responses within the scope of parasocial relationship theory. Parasocial relationship refers to the one-sided interpersonal relationships individuals establish with celebrities in the media (Sakib et al, 2019).…”
Section: Extended Abstractmentioning
confidence: 99%
“…Emplear celebridades, consumidores típicos, expertos profesionales, empleados de la empresa o voceros anónimos como prescriptores publicitarios es una estrategia recurrente entre los anunciantes (Perelló-Oliver et al, 2018;Schouten et al, 2020;Tran et al, 2019), ya que imbuyen de personalidad a las marcas y maximizan el impacto persuasivo del mensaje. El objetivo es crear una imagen de marca a través de la persona y no del producto en sí, con el fin de capitalizar la confianza percibida de los consumidores potenciales (Mospan & Alexander, 2018).…”
Section: Patrocinadores En La Publicidad Radiofónicaunclassified
“…Los prescriptores se consideran una fuente de credibilidad. McCroskey y Young (1981) indicaron que la credibilidad es una actitud hacia la fuente de información, que modifica la aceptación del mensaje (Schouten et al, 2020;Tran et al, 2019) y el grado de acuerdo con el mismo. Por tanto, en la medida en que los mensajes no puedan recibirse fuera de su fuente, la credibilidad es un factor decisivo en la eficacia de la persuasión (Morimoto, 2020;Plasek & Temesi, 2019).…”
Section: Patrocinadores En La Publicidad De Complementos Alimenticiosunclassified